Perencanaan, Perencanaan Kontingensi dan Hubungannya dengan Work From Home - Abdul Ghani; Arif Prayogo; Asma Ivadati; Sumbulatun Sumbulatun; Hadi Supratikta (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research aims to investigate, analyze and understand how planning and contingency planning can be linked to the implementation and management of Work from Home (WFH) policies in organizations. The results of research on planning, contingency planning and its relationship with work from home (WFH) include: a) Mature planning supports WFH success: Companies with mature and structured planning tend to be better prepared to face challenges and take advantage of the benefits of the WFH work model.b )Contingency Planning is Important: Preparedness in dealing with emergency situations or sudden changes is key in the successful implementation of WFH.c)Positive Correlation between Planning and WFH Effectiveness: A positive correlation is seen between the level of thorough planning and the level of effectiveness and productivity in a WFH work environment. D)Challenges in WFH Require Creative Solutions: While strong planning is important, communication, collaboration and company culture challenges remain the primary focus in a WFH environment.